Breakdown of Curly Arrow Rules in Anthraquinone. Issue 46 (15th October 2018) - Alqahtani, Jehan; Sadeghi, Hatef; Sangtarash, Sara; Lambert, Colin J.
Abstract: Understanding and controlling quantum interference (QI) in single molecules is fundamental to the development of QI‐based single‐molecule electronics. Simple rules such as counting rules, curly arrow rules (CARs), circuit rules, and more recently magic ratio rules have been developed to predict QI patterns in polycyclic aromatic hydrocarbons. CARs are widely used to predict destructive QI. Here we examine the validity of CARs in fully conjugated anthracene and dihydroxyanthracene, cross‐conjugated anthraquinone, and broken conjugated dihydroanthracene attached to either graphene or gold electrodes through π‐π stacking or thiol and Au−C anchors. For the first time, we demonstrate that CARs break down in molecular junctions formed by cross‐conjugated anthraquinone. In contrast with the destructive QI predicted by CARs for a meta ‐connected anthraquinone core, we demonstrate that QI is constructive. This behavior is independent of the choice of electrode material or anchor groups. This is significant, because by changing the redox state of meta ‐connected dihydroxyanthracene to form meta ‐connected anthraquinone, the conductance of the junction increases by a couple of orders of magnitude due to the crossover from constructive to destructive QI. This opens new avenues for realization of QI‐based single‐molecule switches. Abstract : Short and curly : Curly arrow rules break down in molecular junctions formed by cross‐conjugated anthraquinone. In contrast with the destructive quantum interference (QI) predicted by curly arrow rules for a meta ‐connected anthraquinone core, it is demonstrated here that QI is constructive.